2004
DOI: 10.1124/jpet.104.079855
|View full text |Cite
|
Sign up to set email alerts
|

AMG 9810 [(E)-3-(4-t-Butylphenyl)-N-(2,3-dihydrobenzo[b][1,4] dioxin-6-yl)acrylamide], a Novel Vanilloid Receptor 1 (TRPV1) Antagonist with Antihyperalgesic Properties

Abstract: The vanilloid receptor 1 (VR1 or TRPV1) is a membrane-bound, nonselective cation channel expressed by peripheral sensory neurons. TRPV1 antagonists produce antihyperalgesic effects in animal models of inflammatory and neuropathic pain. Here, we describe the in vitro and in vivo pharmacology of a novel TRPV1 antagonist, AMG 9810,AMG 9810 is a competitive antagonist of capsaicin activation (IC 50 value for human TRPV1, 24.5 Ϯ 15.7 nM; rat TRPV1, 85.6 Ϯ 39.4 nM) and blocks all known modes of TRPV1 activation, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
272
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(289 citation statements)
references
References 40 publications
15
272
0
2
Order By: Relevance
“…However, in these animals, mechanical allodynia associated with both inflammation and nerve injury remained unchanged. In contrast to these results, several novel TRPV1 antagonists,piperazine-1-carboxamide (BCTC) (Pomonis et al, 2003), AMG 9810 [(E)-3-(4-tert-butylphenyl)-N-(2,3-dihydrobenzo[b] [1,4] dioxin-6-yl)acrylamide] (Gavva et al, 2005), and A-425619 [1-isoquinolin-5-yl-3-(4-trifluoromethyl-benzyl) -urea] Honore et al, 2005), have demonstrated efficacy in reducing thermal hyperalgesia and mechanical allodynia associated with both chronic inflammation and neuropathy in rats. Together, these studies suggest that TRPV1 plays an important role in integrating multiple pain-producing stimuli.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, in these animals, mechanical allodynia associated with both inflammation and nerve injury remained unchanged. In contrast to these results, several novel TRPV1 antagonists,piperazine-1-carboxamide (BCTC) (Pomonis et al, 2003), AMG 9810 [(E)-3-(4-tert-butylphenyl)-N-(2,3-dihydrobenzo[b] [1,4] dioxin-6-yl)acrylamide] (Gavva et al, 2005), and A-425619 [1-isoquinolin-5-yl-3-(4-trifluoromethyl-benzyl) -urea] Honore et al, 2005), have demonstrated efficacy in reducing thermal hyperalgesia and mechanical allodynia associated with both chronic inflammation and neuropathy in rats. Together, these studies suggest that TRPV1 plays an important role in integrating multiple pain-producing stimuli.…”
Section: Introductionmentioning
confidence: 80%
“…Several other novel selective TRPV1 antagonists (e.g., capsazepine, BCTC, and AMG 9810) have been reported to reduce mechanical allodynia associated with inflammation (Pomonis et al, 2003;Walker et al, 2003;Gavva et al, 2005). In contrast, mechanical allodynia associated with inflammation developed normally in TRPV1 knock-out mice (Caterina et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…To exclude the interference by classical 5-HT receptors, we included Y-25130 (200 nM) and methysergide (40 M) in the recording solution to block 5-HT 3 and 5-HT 1,2,7 receptors (Yakushiji and Akaike, 1992; Dahlöf and Maassen Van Den Brink, 2012), respectively. We also included AMG9810 (10 M), a TRPV1 selective antagonist, to block proton-induced TRPV1 activation (Gavva et al, 2005). Under these conditions, the prevalent type of currents induced by the pH 5.0 solution among small-and medium-sized (15-30 m) WT mouse DRG neurons were ASIC-like (rapidly inactivating in response to acid; 79.4%, 27 of 34 total tested neurons) (Fig.…”
Section: -Ht Enhances Ph 50-induced Currents and Excitability Of Drmentioning
confidence: 99%
“…Some endogenous ligands termed endovanilloids (3), including 15-hydroperoxyeicosa-5Z,8Z,11Z,13E-tetraenoic acid (15(S)-HPETE), a lipoxygenase product, also activate TRPV1 (4). Because mice genetically lacking the TRPV1 channel exhibit impaired nociception (5,6) and several TRPV1 antagonists have antinociceptive activity in vivo (7)(8)(9), TRPV1 is considered to be a key component of signal transduction pathways in the nociceptive system. Several regulatory mechanisms of TRPV1 function have been elucidated.…”
mentioning
confidence: 99%